Handbook of sea-level research - Shennan, Ian.; Long, Antony; Horton, B. P. (Benjamin P.) (Hoboken, NJ : Wiley-Blackwell, 2015)
"This book will cover all aspects of modern sea-level studies, with a focus on the most robust scientific approaches and techniques"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Sea level -- Research; Climatic changes; SCIENCE / Earth Sciences / Oceanography; Climatic changes; Sea level -- Research; Electronic books; Electronic books